Sports Charity and Gendered Labour - Palmer, Catherine (Emerald Studies in Sport and Gender, 2021)
Sports Charity and Gendered Labourprovides examples for teaching and knowledge sharing across analyses of gender, sport, leisure, health and wellbeing in ways that will have broad relevance to a range of audiences.